Analisis Normatif terhadap Penyebaran Deepfake Sebagai Bentuk Kejahatan Siber di Indonesia - Fabrizio Richardo Marvil Wanggai; Made Sugi Hartono; Ni Putu Ega Parwati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The rapid development of artificial intelligence technology, particularly deepfake, poses significant challenges to legal protection due to its potential misuse for identity manipulation, defamation, and other cybercrimes. This phenomenon highlights a gap between technological advancement and the readiness of legal regulations in Indonesia. This study aims to analyze forms of deepfake misuse and to assess the effectiveness of existing legal frameworks in providing legal protection and certainty. The research employs a normative legal method using statutory and conceptual approaches by examining legislation, legal doctrines, and relevant scholarly literature. The findings indicate that Indonesian positive law does not yet specifically regulate deepfake technology, resulting in law enforcement relying on general provisions of criminal law and the Electronic Information and Transactions Law. The implications of this study emphasize the urgency of regulatory reform and the formulation of adaptive legal policies to address digital technological developments in order to ensure legal protection and justice for society.